Native parasitoids associated with Tuta absoluta in the tomato production areas of the Spanish Mediterranean Coast - Gabarra, Rosa; Arnó, Judit; Lara Acedo, Lidia; Verdú, María J.; Ribes, Antoni; Beitia, Francisco J.; Urbaneja, Alberto; Téllez-Navarro, María M.; Mollá-Hernández, Óscar; Riudavets, Jordi (2017)
The tomato borer Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) is an invasive pest that produces significant damage to tomato crops in the Mediterranean area. Although several species of predatory bugs are successfully being used for biological control of the pest, little is known about the parasitoids that are able to exploit T. absoluta as a host. With the aim of better understanding parasitoid species richness of T. absoluta along the Mediterranean Spanish Coast, we conducted an extensive survey to determine distribution, host plants and habitats where parasitoids are present. Our results indicated that egg parasitoids are naturally scarce but that the species richness of larval/pupal parasitoids is high and includes 20 different species. Seven of these had not been previously reported as T. absoluta parasitoids. The most frequent parasitoid species recovered were Necremnus sp. nr. artynes (Walker), Stenomesius cf. japonicus (Ashmead) and Neochrysocharis formosa (Westwood) (Hymenoptera: Eulophidae).